Predicting development of adolescent drinking behaviour from whole brain structure at 14 years of age - Kühn, Simone; Mascharek, Anna; Banaschewski, Tobias; Bodke, Arun; Bromberg, Uli; Büchel, Christian; Quinlan, Erin Burke; Desrivieres, Sylvane; Flor, Herta; Grigis, Antoine; Garavan, Hugh; Gowland, Penny A; et al. (eLife, 2019)
Adolescence is a common time for initiation of alcohol use and development of alcohol use disorders. The present study investigates neuroanatomical predictors for trajectories of future alcohol use based on a novel voxel-wise whole-brain structural equation modeling framework. In 1814 healthy adolescents of the IMAGEN sample, the Alcohol Use Disorder Identification Test (AUDIT) was acquired at three measurement occasions across five years. Based on a two-part latent growth curve model, we conducted whole-brain analyses on structural MRI data at age 14, predicting change in alcohol use score over time. Higher grey-matter volumes in the caudate nucleus and the left cerebellum at age 14 years were predictive of stronger increase in alcohol use score over 5 years. The study is the first to demonstrate the feasibility of running separate voxel-wise structural equation models thereby opening new avenues for data analysis in brain imaging.
Gesehen am 02.08.2019